Dampak Customer Relationship Management Terhadap Kepuasan Nasabah dan Loyalitas Nasabah PT.Bank Rakyat Indonesia (Persero) Tbk Cabang Penunjang Bener Meriah - Putra, Yunanda Eka (Widya Balina, 2023)
This study uses Structural Equation Modeling (SEM) and random and proportional stratification methods to determine how customer relationship management impacts customer satisfaction and customer loyalty in PT. Bank Rakyat Indonesia (Persero), Tbk Bener Meriah Sub-Branch Office. The number of samples used was 250 people. The results showed that customer relationship management had a significant effect on both customer satisfaction and customer loyalty at PT. Bank Rakyat Indonesia (Persero), Tbk Bener Meriah Sub-Branch Office. In addition, customer satisfaction serves as a partial mediator between the influence of customer relationship management on customer loyalty.